Use of Virtual Video Call Communications in Family Visits: A Literature Review - Nila Fitri; Agung Waluyo; Riri Maria (STIKep PPNI Jawa Barat, 2021)
Background: Family visits and patient assistance by the family during treatment experience limitations. limitations occur because of the COVID-19 pandemic which eliminated all family visits to patients, patients being treated in isolation rooms, elderly people living in nursing homes, and family limitations in visiting their cared for families. Objective: Online visitation with a video call between patient and family can reduce the harm of isolation. Method: The writing method uses a literature review to summarize and conclude several studies using video calls for family visitations in patients both hospitalized and elderly in nursing homes. Journal searches are carried out through both national and international databases. Search for related journals using the EBSCO, Pubmed, Proquest, Elsevier and Google Scholar databases. Result: From the literature search, it was found that the use of video calls for online visitations of patients in hospitals and the elderly in nursing homes showed a decrease in anxiety, increased morale, reduced feelings of loneliness and isolation.